Frithjof Schuon’un hayatı, eserleri ve tasavvufi görüşleri - Çiçek, Betül Özel (My University, 2007)
FRITHJOF SCHUON’UN HAYATI, ESERLERİ VE TASAVVUFÎ GÖRÜŞLERİ TEZ ÖZETİ Frithjof Schuon, yirmibirinci yüzyılın önde gelen Tradisyonelistlerindendir. René Guénon ve Ananda Coomaraswamy’nın başlattığı Tradisyonel ekolün üçüncü ve birleştirici halkasıdır. “Dinlerin aşkın birliği” ve “religio perennis” kavramlarını ortaya koymuştur. Schuon’ün yaşarken kamuya çok duyurulmamış bir yönü Şâzelî tarikatının Alevîyye kolundan bir tasavvuf şeyhi olmasıdır. 1932’de Cezayir’e giden Schuon, burada Şeyh Ahmed el-Alevî ile tanışarak Alevîyye tarîkatına intisâb etmiştir. Bu tarîkatın Paris’teki mukaddemliğini yapmış ve daha sonra aldığı ilâhî ilhamla şeyhlik mertebesine yükselmiştir. 1950lerde ise Meryemîyye tarîkatını kurmuştur. Zannedilenin aksine, Frithjof Schuon’ün “dinlerin aşkın birliği”ne ve kalp dili dediği “religio perennis” yaptığı vurgu, İslâm dininin yahut herhangi vahyî bir dinin zâhirî unsurlarını gözardı etmesine sebep olmamıştır. 1998 yılında vefat eden Frithjof Schuon’ün dünyanın dört bir yanında mürît ve takipçileri bulunmaktadır. thjof Schuon, Meryemîyye tarîkatı, religio perennis.

Frithjof Schuon is one of the most eminent Traditionalists of the twenty-first century. He is the third and unifying chain of the Traditionalist school, pioneers of which are René Guénon and Ananda Coomaraswamy. Frithjof Schuon is the main expositor who coined the terms “transcendent unity of religions” and “religio perennis”. What was not known commonly when Schuon was alive is his being a Sufi master belonging to Alevîyye branch of Şâzelî tariqah. Frithjof Schuon had gone to Cezayir in 1932 where he met Sheikh Ahmed el-Alevî by the hand of whom he got initiated into the Alevîyye. He was appointed as the muqaddem of the tariqah in Paris. After a while, with a divine grace and inspiration he became a Sheikh. At 1950s, he established his own tariqah, Meryemiyye. Contrary to the assumptions, Schuon’s emphasis on “transcendent unity of religions” and “religio perennis” which he liked to call “the religion of the heart”, never caused him to be less than most respectful to the outward aspect of Islam or any other revealed religion. Frithjof Schuon who died in 1998, had many followers and disciples all over the world. Key Words: Frithjof Schuon, Meryemîyye tariqah, religio perennis.
Keywords: İslam Dini; Tasavvuf